2008
DOI: 10.1104/pp.108.118919
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor VvMYB5b Contributes to the Regulation of Anthocyanin and Proanthocyanidin Biosynthesis in Developing Grape Berries    

Abstract: Among the dramatic changes occurring during grape berry (Vitis vinifera) development, those affecting the flavonoid pathway have provoked a number of investigations in the last 10 years. In addition to producing several compounds involved in the protection of the berry and the dissemination of the seeds, final products of this pathway also play a critical role in berry and wine quality. In this article, we describe the cloning and functional characterization of VvMYB5b, a cDNA isolated from a grape berry (V. v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
374
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(399 citation statements)
references
References 64 publications
24
374
0
1
Order By: Relevance
“…The current model for the regulation of PA biosynthesis is mainly based on results from Arabidopsis, where TT2, TT8, and TTG1 form a ternary complex to activate PA biosynthesis genes (Baudry et al, 2004). In grape, VvMYB5a and VvMYB5b can activate the VvANR promoter in the presence of AtEGL3, suggesting that MYB5 proteins are also part of a similar ternary complex (Deluc et al, 2008). In our transactivation assays using Arabidopsis protoplasts, we observed that MtMYB5 and MtMYB14 alone can weakly activate both the ANR and LAR promoters, with MYB5 showing somewhat higher activity than MYB14.…”
Section: Downstream Targets Of Myb5 and Myb14 In M Truncatulamentioning
confidence: 99%
See 1 more Smart Citation
“…The current model for the regulation of PA biosynthesis is mainly based on results from Arabidopsis, where TT2, TT8, and TTG1 form a ternary complex to activate PA biosynthesis genes (Baudry et al, 2004). In grape, VvMYB5a and VvMYB5b can activate the VvANR promoter in the presence of AtEGL3, suggesting that MYB5 proteins are also part of a similar ternary complex (Deluc et al, 2008). In our transactivation assays using Arabidopsis protoplasts, we observed that MtMYB5 and MtMYB14 alone can weakly activate both the ANR and LAR promoters, with MYB5 showing somewhat higher activity than MYB14.…”
Section: Downstream Targets Of Myb5 and Myb14 In M Truncatulamentioning
confidence: 99%
“…AtMYB5, a MYB transcription factor regulating trichome branching in leaves and mucilage accumulation in seed coats, plays only a minor role in PA biosynthesis in Arabidopsis (Gonzalez et al, 2009;Li et al, 2009). However, overexpression of VvMYB5a and VvMYB5b (the homologs of AtMYB5 in grape [Vitis vinifera]) in tobacco (Nicotiana tabacum) induces PA accumulation in flowers (Deluc et al, 2006(Deluc et al, , 2008. DkMYB4 (the homolog of AtMYB5 in persimmon [Diospyros kaki]) has been demonstrated to regulate PA accumulation in persimmon fruits, and overexpression or knockdown of DkMYB4 induces or reduces, respectively, PA accumulation in persimmon callus.…”
mentioning
confidence: 99%
“…However, grape was subsequently shown to also use a TT2-like MYB (VvMYBPA2) to regulate PAs in berries, which works in concert with VvMYBPA1 (Terrier et al, 2009). A third type of MYB transcription factor involved in PA synthesis is the MYB5a/b proteins from grapevine (Deluc et al, 2008), but these MYB proteins appear to be less specific than MYBPA1 and MYBPA2. Anthocyanin regulatory MYBs (VvMYBA1/2) have also been characterized in grape (Kobayashi et al, 2002).…”
Section: Vcmybpa1 Phylogeny and Expression Pattern Suggest A Role Inmentioning
confidence: 99%
“…Therefore, in addition to activating PA synthesis early in development, these MYBs may also contribute to anthocyanin synthesis later during ripening via the activation of general flavonoid genes. This would likely necessitate a negative regulator of PA-specific genes during ripening to prevent reactivation of the PA pathway (Deluc et al, 2008). Further work is necessary to unequivocally demonstrate the functionality and specificity of VcMYBPA1 in the context of blueberry fruit development.…”
Section: Vcmybpa1 Phylogeny and Expression Pattern Suggest A Role Inmentioning
confidence: 99%
“…The bHLH proteins may have overlapping regulatory targets (Zimmermann et al, 2004), but MYB proteins are believed to be key components by allocation of specific gene expression patterns (Stracke et al, 2001). In grape berries, the MYB proteins MYBA1 and MYBA2 (Kobayashi et al, 2002;Walker et al, 2007), MYB5a (Deluc et al, 2006), MYB5b (Deluc et al, 2008), and MYBPA1 act together with bHLH proteins and probably WDR proteins to control anthocyanin and/or PA synthesis. Most R2R3-MYB factors regulating flavonoid biosynthesis (except flavonol synthesis) depend on cofactors, including WDR proteins but, most importantly, a small subgroup of bHLH proteins that share a common motif in their N termini that interacts with a signature motif in the R3 repeat of the N-terminal R2R3 domain of MYB factors (Grotewold et al, 2000).…”
mentioning
confidence: 99%